2021
DOI: 10.1101/2021.01.18.21250049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the effect of information channel on COVID-19 vaccine acceptance

Abstract: Hesitancy towards the COVID-19 vaccine remains high among the US population. Now that the vaccine is available to priority populations, it is critical to convince those that are hesitant to take the vaccine. Public health communication about the vaccine as well as misinformation on the vaccine occurs through a variety of different information channels. Some channels of information are more commonly found to spread misinformation. Given the expansive information environment, we sought to characterize the use of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Moreover, the selected studies in this review are subject to volunteer bias, where participants who actively decide to participate in the research may systematically differ from the general population [143] . Furthermore, our systematic search did not capture the studies that specifically addressed the influence of social media on people's intention to vaccinate, such as the study conducted in the UK [144] and in the US [145] , However, it did identify one survey that included adults as representatives of social media users and found a surprisingly high vaccine acceptance rate among this population, which might not reflect the real picture related to this issue. Thus, future systematic reviews that will aim to address the problem of hesitancy associated with COVID-19 vaccine should take these studies into consideration as well when designing their search criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the selected studies in this review are subject to volunteer bias, where participants who actively decide to participate in the research may systematically differ from the general population [143] . Furthermore, our systematic search did not capture the studies that specifically addressed the influence of social media on people's intention to vaccinate, such as the study conducted in the UK [144] and in the US [145] , However, it did identify one survey that included adults as representatives of social media users and found a surprisingly high vaccine acceptance rate among this population, which might not reflect the real picture related to this issue. Thus, future systematic reviews that will aim to address the problem of hesitancy associated with COVID-19 vaccine should take these studies into consideration as well when designing their search criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that those who hold such beliefs tend to also distrust the government, news media, and scientists, attempts to address those beliefs by using the same types of sources these individuals distrust is fraught with challenges. Though we did not directly measure it, social media consumption (as opposed to mainstream media) as a primary source of information has been shown to be more predictive of COVID vaccine hesitancy (Jennings et al, 2021;Piltch-Loeb et al, 2021). Whether attempts to flag misinformation in social media posts (as recently done by several social media companies) has the potential to alter people's beliefs in conspiracy theories and pseudoscience, and in which direction, is still an open research question.…”
Section: Discussionmentioning
confidence: 96%
“…There is some existing evidence that, when it comes to disease and vaccination, vaccine hesitant individuals (those who possess vaccine-related concerns that cause them to forego vaccination currently, regardless of whether they eventually choose to vaccinate) often tend to be less trusting of information put forth by various entities (e.g., doctors, experts; Yaqub et al, 2014). As it concerns COVID-19 specifically, there is also evidence that people vary in the amount of trust they place in information received from various sources (e.g., media, scientists, healthcare professionals; El-Elimat et al, 2021;Fridman et al, 2021;Murphy et al, 2021;Piltch-Loeb et al, 2021). Prior research has shown that the more trust individuals put into the government, scientists, and healthcare professionals, the less likely they are to be COVID vaccine hesitant.…”
Section: Trust In Information and Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several factors significantly associated with the vaccine uptake while the population's acceptability of the vaccine will most likely be influenced by their socioeconomic status, perceptions, trust, beliefs, vaccines-related knowledge and information about the trustworthiness of vaccines, side effects of the vaccine and the importance of the vaccine to prevent the health consequences of COVID-19. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Every country tries to flatten the COVID-19 epidemic curve with the ultimate goal of accepting vaccines against coronavirus. In the meantime, Myanmar's coronavirus prevention measures have been collapsed since February 2021.…”
Section: Introductionmentioning
confidence: 99%